Anti-microbial and anti-inflammatory activities of crude and acidified fraction of selected Malaysian honey samples - Nurul Izzati Mohd. Ismail, 1988- author; Chua, Lee Suan, supervisor; Fakulti Kejuruteraan Kimia (2015)
Thesis (Sarjana Kejuruteraan (Bioproses)) - Universiti Teknologi Malaysia, 2015